TURKISH COOPERATION AND COORDINATION AGENCY (TİKA) IN CENTRAL ASIA: DEVELOPMENT COOPERATION, SOFT POWER, AND THE DYNAMICS OF REGIONAL INFLUENCE - Azamat Sharipov (International Journal of Literature and Language Studies, 2026)
Abstract. This article analyses the activities of the Turkish Cooperation and Coordination Agency (TİKA) in the states of Central Asia within the framework of development-cooperation and soft-power theory. The study spans the period from 1992 to 2023 and draws on data from the OECD and the World Bank, as well as on scholarly sources indexed in the Scopus and JSTOR databases. The article examines the agency’s institutional evolution, the dynamics of the financial flows directed to the region, and their interrelationship with the objectives of Turkish foreign policy, considered on a year-by-year basis.